Sleep quality and stress as influences on college students’ physical activity participation: a cross-sectional study - Wang, Hao; Zhao, Shiqi; Fang, Tianle; Xiao, Lishun; Yin, Dehui; Sun, Zhiming (Frontiers in Public Health, 2025)
ObjectiveThis study examines the relationship between sleep, stress, and exercise among college students, as these factors are significantly associated with their well-being, academic performance, and quality of life. Understanding their interconnections is crucial for promoting healthy behaviors.MethodsConducted from March to April 2025 at Xuzhou Medical University, the study involved distributing 840 electronic questionnaires to undergraduate, graduate, and doctoral students, yielding 796 valid responses (94.76% response rate). We used the Physical Activity Rating Scale-3 (PARS-3), Perceived Stress Scale (PSS-14), and Athens Insomnia Scale (AIS) to assess physical activity, stress, and sleep quality, respectively. Statistical analyses included multifactorial ANOVA, Spearman’s correlation, mediation analysis, and multiple linear regression using SPSS 27.0.ResultsMale students had higher participation in medium- and large-scale sports than females. Second-year students showed lower participation rates. Obese or overweight students had higher participation in these sports. Both sleep quality and stress were significantly associated with exercise levels. There was an inverse relationship between exercise levels and stress, and between exercise levels and sleep quality. Stress was involved in the association between sleep quality and exercise level, confirmed by mediation analysis. Multiple linear regression further supported the significant association of stress and sleep quality with exercise levels.ConclusionSleep quality and stress levels are key factors associated with exercise participation among college students. Tailored health education and interventions are essential to improve students’ well-being. Future longitudinal studies are needed to establish causality and explore additional influencing factors.